Digital Communications in Public Administration: Essence, Role and Requirements for Formation - Hrynchak N. А.; Syniakov, A. V. (Statistics of Ukraine, 2023)
The article examines the essence and role of digital communications in public administration. It was determined that the main tasks of communications in public administration are informing the public and explaining the actions taken; promoting and strengthening institutional action and facilitating the discussion of ideas. In the face of digital transformation, public authorities have more ways than ever to communicate with communities — from social networks and online town halls to chatbots and virtual assistants. The types of digital communications that have gained widespread practical application by public authorities in the conditions of digital transformation are singled out. It is substantiated that the main requirements for building an effective system of digital communications in public administration are inclusiveness, bilateralism and persuasiveness. Public communication that ignores the differences in how different social groups respond to news and information, or which messages will resonate with whom, is likely to have limited reach and impact. The priority for public authorities should be the development of communication that would be better suited to different groups of the population. Public authorities are increasingly striving to establish two-way communication, when they are both senders and receivers of messages, as a means of achieving a certain form of permanent dialogue with citizens and stakeholders. The persuasiveness of communications depends not only on how they are designed. Trust in the source of information is especially important. Understanding how trust factors can be integrated into the development of communication strategies and initiatives in a way that promotes greater public acceptance and, in turn, compliance requires further research.